The Preservation and Conservation of Old Shophouses in Kajang Town, Selangor, Malaysia - Murtza, Muhammad Hamidy; Shukri, Sharyzee Mohmad; Taib, Idris; Aziz, Adrianta (MAJ - Malaysia Architectural Journal, 2021)
The old shophouse in Kajang town is the best example of Hulu Langat district for historical buildings in the 20th century. Kajang town, Selangor, was selected for the case study shown, seeing as the high value of wealth history of colonial-era buildings. However, the original identity of the shophouses nowadays continues to be endangered by urban development due to the demand for infrastructure development and buildings where involved the changes of images and alter the urban pattern of the city like many other cities modernisation at a rapid and unchecked pace. This paper aims to discuss the significance and clarify the issues of shophouses at Kajang town and involves main factors of site, building facade design and historical influences to ensure it is preserved and conserved for the future. However, the discussion is not focusing on the building facade, but the environmental factors must be taken as cause damage to the building. This research method employs a site observation, historical map overlay, and literature review to understand the heritage shophouses in Kajang town. These identified issues should be emphasised with the effective methods that may apply to the overall rehabilitation design planning to find out about guidelines to specific articulations for conservation and recommendations of Kajang shophouses.